A study of the guidance services in private universities of the Philippines - Parayno, Corazon C. 1931- (University of the Philippines], 1955)
The nature and extent of guidance services obtained in the private universities of the Philippines are determined in this study. This includes the organization of the guidance program, the persons qualified to carry on counseling and their training, and the extent that such counseling measures are used in dealing with adjustment problems.